Models of collaborative governance: The city of Los Angeles' foreclosure registry program - Helen Morales; Jack Meek (Administrative Sciences, 2019)
The economic recession of 2007-2013 brought many challenges to nations and cities throughout the world. Los Angeles experienced a foreclosure crisis that brought instability in the real property market, resulting in property loss and loss of revenue from property taxes and increasing demands on city resources from blighted properties. The paper begins with a background of the problem related to blighted properties and proceeds a literature review related to the five phases to the development and implementation of a governance network. The paper then examines a case study-the City of Los Angeles Foreclosure Registry Program's governance network to reduce blight-to assess the phases taken to learn if the theory of network design offers meaningful direction and insight. The paper closes with an evaluation of the consistency regarding the literature related to the five phases of governance network development and its implementation by the City of Los Angeles.
Keywords: 350; collaboration; governance networks; metropolitan administration; housing